Surface-modified silicone T-tubes for prevention of tracheal stenosis in a rabbit model - Choi, Jeong-Seok; Lim, Jae-Yol; Park, In S.; Seo, Si Y.; Joung, Yoon K.; Han, Dong K.; Kim, Young-Mo (WILEY, 2015)
Objectives/HypothesisThis study was conducted to determine whether a surface-modified tracheal T-tube can prevent tracheal stenosis in a rabbit model. Study DesignAnimal model study. MethodsWe designed surface-modified tracheal T-tubes in which silicone rubber was modified by coating it with hyaluronic acid (HA) or polyethylene glycol (PEG). Sixteen rabbits were divided into four insertion groups: normal, silicone tube, silicone tube coated with HA, and silicone tube coated with PEG. Surface-modified tubes were inserted into the tracheal lumen after a scraping injury on the inner tracheal mucosa around the preformed tracheostoma. Laryngoscopy was performed to evaluate formation of stenosis in the trachea. Histological examinations were performed to evaluate epithelial thickness, inflammatory response, and fibrosis. ResultsEndoscopic finding showed that the HA- and PEG-coated tube groups had less granulation tissue in the trachea than the noncoated tube group. Greater epithelialization was observed in the noncoated tube group than in the normal group. HA- and PEG-coated tube groups showed a tendency to decreasing epithelialization compared with the noncoated tube group. More inflammatory cells were observed in the noncoated tube group than in the normal group, and fewer inflammatory cells were observed in the HA- and PEG-coated tube groups than in the noncoated tube group. The noncoated tube group showed a greater area of fibrosis than the HA- and PEG-coated tube groups. ConclusionsA surface-modified tracheal T-tube may have a favorable effect on reducing tracheal stenosis in a rabbit model. We suggest that local application of HA and PEG should be further researched for prevention of tracheal stenosis. Our rabbit model could be helpful in providing an additional scenario for evaluating new strategies to prevent tracheal stenosis. Level of EvidenceNA Laryngoscope, 125:1465-1471, 2015
Keywords: HYALURONIC-ACID; POLYETHYLENE-GLYCOL; IN-VITRO; SODIUM HYALURONATE; MITOMYCIN-C; SURGERY; STENT; COMPLICATIONS; PEGYLATION; MANAGEMENT